PSYCHOLOGY VERSUS PEDAGOGY: PRO ET CONTRA - MAZILOV, VLADIMIR (Main Issues Of Pedagogy And Psychology, 2018)
The article discusses the problems of lifelong learning. It is noted that the insufficient attention to psychology is a significant obstacle for the development of education in Russia. It is argued that in modern Russian school insufficient attention is paid to the organization of understanding, as a result of which knowledge acquisition is suffering. It is proposed to organize school education taking into account the patterns of understanding.